RESEARCH ON THE COSMETIC PRODUCTS MARKET IN ORADEA. PRACTICAL STUDY - Oana Maria SECARĂ (Annals of the University of Oradea: Economic Science)
This paper was carried out with the aim of determining the preferences of consumers in the municipality of Oradea, with regard to cosmetic products, marketed by both multinational companies and local ones in Romania. Also, as a result of the study carried out on a simple, non-stratified representative sample, data were obtained regarding the purchase locations, the factors that influence their purchase decisions, the frequency of purchase and use of cosmetic products, as well as the brands and types of products preferred by to them. In order to carry out this study, a questionnaire with closed dichotomous, multichotomies and mixed questions was created, which was applied to a representative sample of 250 subjects, residents of the municipality of Oradea.